Adolescent Disclosure to Parents and Daily Management of Type 1 Diabetes. (6th August 2016) - Berg, Cynthia A.; Queen, Tara; Butner, Jonathan E.; Turner, Sara L.; Hughes Lansing, Amy; Main, Alexandra; Anderson, Jessica H.; Thoma, Brian C.; Winnick, Joel B.; Wiebe, Deborah J.
Abstract : Objective To examine how adolescents' daily disclosure to parents about type 1 diabetes management may foster a process whereby parents gain knowledge and are viewed as helpful in ways that may aid diabetes management. Methods A total of 236 late adolescents ( M age = 17.76) completed a 14-day diary where they reported daily disclosure to, and solicitation from, their parents, how knowledgeable and helpful parents were, and their self-regulation failures and adherence; blood glucose was gathered from meters. Results Multilevel models revealed that adolescent disclosure occurred in the context of greater parent solicitation and face-to-face contact and was positively associated with adolescents' perceptions of parental knowledge and helpfulness. Disclosure to mothers (but not to fathers) was associated with better diabetes management (fewer self-regulation failures, better adherence). Conclusions Adolescent disclosure may be an important way that parents remain knowledgeable about diabetes management and provide assistance that serves to support diabetes management.